Drug Delivery and Targeting to the Brain Through Nasal Route: Mechanisms, Applications and Challenges - Kashyap, Kanchan; Shukla, Rahul (Current Drug Delivery, 2019)
Blood-brain barrier (BBB) provides restrictions for the transportation of various therapeutic agents to the brain. Efforts to directly target the brain by olfactory as well as trigeminal nerve pathway, bypassing BBB, have grown significantly in recent times. The intranasal route of transportation of the drug encompasses ability for the delivery of drug directly to the brain, improves site-specificity in the brain and avoids systemic side effects. In the current era, novel drug delivery systems are useful tools for targeting the brain without providing any harmful effects in nasal mucosa as well as the central nervous system. The complex structure of nasal cavity, mucociliary clearance, degradation by the enzymes present in nasal cavity and pathological conditions like rhinitis, common cold, etc. are the major disputes for nasal drug delivery. The use of nanotechnological approaches like solid lipid nanoparticles, polymeric nanoparticles, nanoemulsions, liposomes and polymeric micelles provides the ability to overcome these barriers. There are several emerging nasal drug delivery technologies produced by various pharmaceutical companies to conquer these hurdles. This review tries to address the recent developments in the area of direct drug delivery to the brain through the nasal route.
Keywords: Blood-brain barrier